Comparative Evaluation Of Analgesic, Antioxidant And Antimicrobial Activities Of Five Selected Medicinal Plants - Venkatappa, Annegowda Hardur (2014)
Plants with medicinal values are known to possess bioactive compounds and contributed greatly to the existence of several currently available pharmaceuticals. In view of this the present study was conducted to evaluate the antioxidant, antinociceptive and antimicrobial activities of traditionally used local plants like Terminalia catappa, Piper betle, Bauhinia purpurea, Cinnamomum iners and Callicarpa furfuracea. In this study sonication, maceration and soxhlet extraction techniques were used to obtain their respective plant extracts. The in vitro antioxidant, antimicrobial activity and polyphenolic content determination revealed the presence of significant biological activities and phenolic content in the extract obtained by sonication followed by maceration and soxhlet extraction. Among the plant extracts studied for antioxidant activity, T. catappa extract showed remarkable antioxidant activity followed by P. betle, B. purpurea, C. iners and C. furfuracea extracts. The antioxidant activity displayed by T. catappa extract was significantly higher than commercially available grape seed extract and synthetic antioxidant butylated hydroxytoluene. In addition, T. catappa extract also revealed marked antimicrobial activity against both Gram-positive and Gram-negative bacterial strains followed by B. purpurea, P. betle and C. iners. Soxhlet ethanolic extract of C. furfuracea leaf, stem and root possessed least polyphenolic content, antioxidant and antimicrobial activities when compared with other plant extracts. This is the first ever study regarding the biological investigations of C. furfuracea.